2023
DOI: 10.2196/43635
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Led Community-Based Support Services and HIV Treatment Outcomes Among People Living With HIV in Wuxi, China: Propensity Score–Matched Analysis of Surveillance Data From 2006 to 2021

Abstract: Background Community-based organizations deliver peer-led support services to people living with HIV. Systematic reviews have found that peer-led community-based support services can improve HIV treatment outcomes; however, few studies have been implemented to evaluate its impact on mortality using long-term follow-up data. Objective We aimed to evaluate the associations between the receipt of peer-led community-based support services and HIV treatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Community-based services help people living with HIV to connect with each other and access programs and services for health and well-being. 47 , 48 While a systematic review and meta-analysis has determined that, overall, HIV infection did not significantly increase risk of COVID-19 mortality, 49 there were fears that the immunodeficiency virus could exacerbate COVID-19 infection. Discrete studies showed upwards of 38% greater risk of severe illness and death due to COVID-19 among people living with HIV compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based services help people living with HIV to connect with each other and access programs and services for health and well-being. 47 , 48 While a systematic review and meta-analysis has determined that, overall, HIV infection did not significantly increase risk of COVID-19 mortality, 49 there were fears that the immunodeficiency virus could exacerbate COVID-19 infection. Discrete studies showed upwards of 38% greater risk of severe illness and death due to COVID-19 among people living with HIV compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants highlighted a certain loss of community during the COVID-19 pandemic, and a desire to gather with their peers once again. The HIV/AIDS epidemic has long been understood as exceptional [45], and a key component of that exceptionalism is the existence of community-based HIV services (e.g., AIDS Committee of Toronto, AIDS Programs South Saskatchewan) in many cities worldwide where people living with HIV can connect with each other and access programs and services for health and well-being [46,47]. While a systematic review and meta-analysis has determined that overall, HIV infection did not significantly increase risk of COVID-19 mortality [48], there were fears that the immunodeficiency virus could exacerbate COVID-19 infection; discrete studies had found upwards of 38% greater risk of severe illness and death due to COVID-19 amongst people living with HIV compared to the general population [49].…”
Section: Resuming In-person Crgtmentioning
confidence: 99%